Art Includes Life, Examples On the Contemporary Interpretation Of Dissident Art - Uz, Ayfer (Atlas Journal, 2023)
Art, which is as old as the history of humanity, has passed through many stages until today, questioning life with its critical side, including its own area of ​​existence, and has come to the present day with new propositions in the reality of change. Art has developed discourses as content other than aesthetic pleasure, touched life, affected people and societies. The critical aspect of art by its nature has continued throughout the ages. Artists questioned themselves, their society, the negative aspects of history and life, intervened in life without sacrificing artistic quality and conveyed this to large masses with their works. The aim of this research is to make an evaluation with the artists who have strikingly revealed their oppositional attitude in contemporary art with their works and influenced the masses, and samples selected from their works. Study; qualitative research method and literature review, the collected data were analyzed with the "descriptive analysis" method and the result was reached.